Tonsillectomy with argon plasma coagulation (APC): evaluation of pain and hemorrhage - Bergler, Wolfgang; Huber, Kerstin; Hammerschmitt, Nicolas; Hörmann, Karl (The laryngoscope, 2001)
Objective Argon plasma coagulation (APC) offers a new possibility for tonsillectomy (TE) because of its effective hemostasis and limited penetration depth of the coagulation zone. The APC dissector allows dissection and hemostasis in a one-step procedure. The aim of this prospective, randomized, single-blinded study was the evaluation of pain and hemorrhage of the “hot” argon-plasma-coagulation tonsillectomy (TEAPC) compared with a conventional “cold” non-electrosurgery tonsillectomy (TEConv). Methods Two hundred one consecutive patients undergoing tonsillectomy were included in a single-blinded, randomized, prospective study with stratification in two age groups. Results There was no statistical significant difference between TEAPC and TEConv in the intensity of postoperative pain and primary or secondary hemorrhage in both age groups. In the TEAPC group, the mean duration of tonsillectomy was significantly reduced by more than 50% in both age groups (P <.01). The blood loss was 90% decreased in the TEAPC compared with the TEConv in both age groups (P <.01). Conclusions The APC technique does not face the general problem of electrosurgery or thermal coagulation techniques in which the postoperative pain is often increased compared with conventional cold techniques. It offers an innovative new tonsillectomy method with significant reduced blood loss and surgical time.